Nash equilibria for non zero-sum ergodic stochastic differential games - Cohen, S; Fedyashov, V (Applied Probability Trust, 2017)
We consider non zero-sum games where multiple players control the drift of a process, and their payoffs depend on its ergodic behaviour. We establish their connection with systems of Ergodic BSDEs, and prove the existence of a Nash equilibrium under the generalised Isaac's conditions. We also study the case of interacting players of different type.